Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

TDP-43 Pathology in the Setting of Intermediate and High Alzheimer's Disease Neuropathologic Changes: A Preliminary Evaluation Across Ethnoracial Groups. - Huie, Emily Z; Escudero, Anthony; Saito, Naomi; Harvey, Danielle; Nguyen, My-Le; Lucot, Katherine L; LaGrande, Jayne; Mungas, Dan; DeCarli, Charles; Lamar, Melissa; Schneider, Julie A; Kapasi, Alifiya; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Transactive Response DNA Binding Protein 43 kDa (TDP-43) pathology is frequently found in cases with Alzheimer's disease (AD). TDP-43 pathology is associated with hippocampal atrophy and greater AD severity denoted by cognition and clinical representation. Current TDP-43 pathology studies are predominantly based on non-Hispanic White cohorts. OBJECTIVE: We sought to evaluate the presence of TDP-43 pathology across ethnoracial groups utilizing the National Alzheimer's Coordinating Center; a database containing data from over 29 institutions across the United States. Cases (N = 1,135: Hispanics/Latinos = 29, African Americans/Black Americans = 51, Asians/Asian Americans = 10, American Indians/Alaskan Natives = 2, non-Hispanic White = 1,043) with intermediate/high AD having data on TDP-43 pathology in the amygdala, hippocampus, entorhinal cortex, and neocortex. METHODS: TDP-43 pathology frequency in each neuroanatomic region among ethnoracial groups were compared using generalized linear mixed effects models with center as a random effect adjusting for age at death, education, and gender. RESULTS: Although groups were imbalanced, there was no significant difference across ethnoracial groups based on TDP-43 pathology (p = 0.84). With respect to neuroanatomical regions evaluated, there were no significant differences across ethnoracial groups (p-values > 0.06). There were also no significant differences for age at death and gender ratios across ethnoracial groups based on TDP-43 pathology. Although not statistically significant, TDP-43 pathology was present less often in Hispanic/Latinos (34%) when compared to non-Hispanic Whites (46%). CONCLUSION: While this is a preliminary evaluation, it highlights the need for diverse cohorts and on TDP-43 pathology research across ethnoracial groups. This is the first study to our knowledge having a focus on the neuroanatomical distribution of TDP-43 deposits in Hispanic/Latino decedents with AD.

Pelargonidin and Berry Intake Association with Alzheimer's Disease Neuropathology: A Community-Based Study. - Agarwal, Puja; Holland, Thomas M; James, Bryan D; Cherian, Laurel J; Aggarwal, Neelum T; Leurgans, Sue E; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2022)
BACKGROUND: An anthocyanidin, pelargonidin, primarily found in berries, has antioxidant and anti-inflammatory properties, and is associated with better cognition and reduced Alzheimer's dementia risk. OBJECTIVE: This study investigated if pelargonidin or berry intake is associated with Alzheimer's disease (AD) neuropathology in human brains. METHODS: The study was conducted among 575 deceased participants (age at death = 91.3±6.1 years; 70% females) of the Rush Memory and Aging Project, with dietary data (assessed using a food frequency questionnaire) and neuropathological evaluations. Calorie-adjusted pelargonidin intake was modeled in quartiles and berry intake as continuous (servings/week). Mean amyloid-beta load and phosphorylated tau neuronal neurofibrillary tangle density across multiple cortical regions were assessed using immunohistochemistry. Global AD pathology burden, a quantitative summary score of neurofibrillary tangles, and diffuse and neuritic plaques using Bielschowsky silver stains in multiple brain regions, was also assessed. RESULTS: In a linear regression model adjusted for age at death, sex, education, APOE ɛ4 status, vitamin E, and vitamin C, participants in the highest quartile of pelargonidin intake when compared to those in the lowest quartile, had less amyloid-β load (β (SE) = -0.293 (0.14), p = 0.038), and fewer phosphorylated tau tangles (β (SE) = -0.310, p = 0.051). Among APOE ɛ4 non-carriers, higher strawberry (β (SE) = -0.227 (0.11), p = 0.037) and pelargonidin (Q4 versus Q1: β (SE) = -0.401 (0.16), p = 0.011; p trend = 0.010) intake was associated with less phosphorylated tau tangles, no association was observed in APOE ɛ4 carriers. Berry intake was not associated with AD pathology. However, excluding participants with dementia or mild cognitive impairment at baseline, strawberry (p = 0.004) and pelargonidin (ptrend = 0.007) intake were associated with fewer phosphorylated tau tangles. CONCLUSION: Higher intake of pelargonidin, a bioactive present in strawberries, is associated with less AD neuropathology, primarily phosphorylated tau tangles.

Association of Amyloid-β Pathology with Decision Making and Scam Susceptibility. - Kapasi, Alifiya; Yu, Lei; Stewart, Christopher; Schneider, Julie A; Bennett, David A; Boyle, Patricia A (J Alzheimers Dis, 2021)
BACKGROUND: Recent findings suggest that poor decision making and increased scam susceptibility are harbingers of Alzheimer's disease (AD) dementia and may be among the earliest behavioral manifestations of pathologic cognitive aging. However, the degree to which poor decision making and scam susceptibility reflect accumulating Alzheimer's disease (AD) pathology remains unclear. OBJECTIVE: To investigate the associations of AD pathology with decision making and scam susceptibility in older adults without dementia. METHODS: Data came from 198 deceased participants without clinical dementia (mean age at death = 90 years; 69%women) from two ongoing studies of aging. All underwent annual clinical evaluations, completed assessments of healthcare and financial decision making and scam susceptibility, and brain donation. Neuropathologic evaluations quantified pathologic hallmarks of AD, amyloid-β and tau-tangles, Lewy body pathology, and TDP-43 proteinopathy. RESULTS: In linear regression models adjusted for demographics, amyloid-β pathology was associated with lower decision making (estimate = -0.35; SE = 0.16, p = 0.03), particularly healthcare decision making (estimate = -0.20; SE = 0.09, p = 0.03), as well as greater scam susceptibility (estimate = 0.12; SE = 0.04, p = 0.003); tau-tangle pathology was not related. Further, TDP-43 pathology was associated with greater scam susceptibility (estimate = 0.10; SE = 0.04; p = 0.02). CONCLUSION: Accumulating AD pathology, particularly amyloid-β, is associated with poor decision making and increased scam susceptibility among older persons without overt cognitive impairment. These findings provide compelling evidence that decision making and scam susceptibility are sensitive to the earliest pathological changes of AD.

MIND Diet, Common Brain Pathologies, and Cognition in Community-Dwelling Older Adults. - Dhana, Klodian; James, Bryan D; Agarwal, Puja; Aggarwal, Neelum T; Cherian, Laurel J; Leurgans, Sue E; Barnes, Lisa L; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2021)
BACKGROUND: MIND diet, a hybrid of the Mediterranean diet and the Dietary Approaches to Stop Hypertension diet, is associated with a slower cognitive decline and lower risk of Alzheimer's disease (AD) dementia in older adults. OBJECTIVE: We aim to examine whether the association of the MIND diet with cognition is independent of common brain pathologies. METHODS: Utilizing data from the Rush Memory and Aging Project (MAP), a longitudinal clinical-pathologic study, we studied 569 decedents with valid dietary data, cognitive testing proximate to death, and complete autopsy data at the time of these analyses. A series of regression analyses were used to examine associations of the MIND diet, dementia-related brain pathologies, and global cognition proximate to death adjusting for age, sex, education, APOEɛ4, late-life cognitive activities, and total energy intake. RESULTS: A higher MIND diet score was associated with better global cognitive functioning proximate to death (β= 0.119, SE = 0.040, p = 0.003), and neither the strength nor the significance of association changed substantially when AD pathology and other brain pathologies were included in the model. The β-estimate after controlling for global AD pathology was 0.111 (SE = 0.037, p = 0.003). The MIND diet-cognition relationship remained significant when we restricted our analysis to individuals without mild cognitive impairment at the baseline (β= 0.121, SE = 0.042, p = 0.005) or in people diagnosed with postmortem diagnosis of AD based on NIA-Reagan consensus recommendations (β= 0.114, SE = 0.050, p = 0.023). CONCLUSION: MIND diet is associated with better cognitive functioning independently of common brain pathology, suggesting that the MIND diet may contribute to cognitive resilience in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid; Autopsy; Brain; Chicago; Cognition; Diet, Mediterranean; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Surveys and Questionnaires

Association of Low Systolic Blood Pressure with Postmortem Amyloid-β and Tau. - Oveisgharan, Shahram; Capuano, Ana W; Kapasi, Alifiya; Buchman, Aron S; Schneider, Julie A; Bennett, David A; Arvanitakis, Zoe (J Alzheimers Dis, 2020)
BACKGROUND: Vascular mechanisms may contribute to the accumulation of AD pathology. OBJECTIVE: We examined whether the burden of vascular risk factors proximate to death is associated with amyloid-β and tau levels or modified their known association. METHODS: We examined the brains of 1, 585 participants from two longitudinal community-based studies of older adults. Amyloid-β and tau were quantified by postmortem examination. The burden of vascular risk factors was summarized by calculating the Framingham general cardiovascular risk score (FRS) proximate to death. Using linear regressions, we examined the association of the FRS with the amyloid-β and tau levels and examined if the FRS modified the association of the amyloid-β with tau. RESULTS: On average, participants were nearly 90 years old and two-thirds were women. The FRS was not associated with amyloid-β (Spearman r  = -0.00, p  = 0.918) or tau (r = 0.01, p = 0.701). However, the FRS as a whole (estimate = -0.022, SE = 0.008, p = 0.009), and specifically the systolic blood pressure (SBP) component (estimate = -0.033, SE = 0.012, p = 0.009), modified the association of the amyloid-β with tau. Further analysis showed that the association between amyloid-β and tau was stronger at lower levels of SBP. CONCLUSION: Late-life vascular risk scores were not related to postmortem levels of amyloid-β or tau. However, lower levels of vascular risk scores and SBP were associated with a stronger association between amyloid-β and tau. These data suggest that vascular risk factors may modify the relation of AD pathology markers to one another.

Neuropathologic Correlates of White Matter Hyperintensities in a Community-Based Cohort of Older Adults. - Arfanakis, Konstantinos; Evia, Arnold M; Leurgans, Sue E; Cardoso, Luis F C; Kulkarni, Arman; Alqam, Nabil; Lopes, Lucas F; Vieira, Diego; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2020)
BACKGROUND: The association of white matter hyperintensities (WMH) with age-related vascular and neurodegenerative pathologies remains incompletely understood. OBJECTIVE: The objective of this work was to elucidate the neuropathologic correlates of WMH in a large community-based cohort of older adults. METHODS: Cerebral hemispheres from 603 community-based older adults were imaged with MRI ex vivo. All participants underwent annual clinical evaluation, cognitive assessment, and neuropathologic examination. WMH burden was assessed using a modified Fazekas rating scale. Multiple ordinal logistic regression was used to test the association of WMH burden with an array of age-related neuropathologies, adjusting for demographics. Mixed effects models of cognition controlling for neuropathologies and demographics were used to determine whether WMH burden contributes to cognitive decline beyond measured pathologies. RESULTS: WMH burden in the whole group was associated with both vascular and Alzheimer's disease (AD) pathologies: arteriolosclerosis (p < 10-4), gross (p < 10-4), and microscopic infarcts (p = 0.04), and amyloid-β plaques (p = 0.028). In non-demented participants (mild or no cognitive impairment) (N = 332), WMH burden was related to gross infarcts (p = 10-4) and arteriolosclerosis (p < 10-4), but not to AD pathology. Similarly, in those with no cognitive impairment (N = 178), WMH burden was related to gross infarcts (p = 8×10-4) and arteriolosclerosis (p = 0.014). WMH burden was associated with faster decline in perceptual speed in both the whole (p = 0.038) and non-demented (p = 0.006) groups. CONCLUSION: WMH burden has independent associations with vascular pathologies in older adults regardless of clinical status, and with AD pathology later in the progression of AD. Moreover, WMH burden may reflect additional tissue injury not captured with traditional neuropathologic indices.

Religious Orders Study and Rush Memory and Aging Project. - Bennett, David A; Buchman, Aron S; Boyle, Patricia A; Barnes, Lisa L; Wilson, Robert S; Schneider, Julie A (J Alzheimers Dis, 2018)
BACKGROUND: The Religious Orders Study and Rush Memory and Aging Project are both ongoing longitudinal clinical-pathologic cohort studies of aging and Alzheimer's disease (AD). OBJECTIVES: To summarize progress over the past five years and its implications for understanding neurodegenerative diseases. METHODS: Participants in both studies are older adults who enroll without dementia and agree to detailed longitudinal clinical evaluations and organ donation. The last review summarized findings through the end of 2011. Here we summarize progress and study findings over the past five years and discuss new directions for how these studies can inform on aging and AD in the future. RESULTS: We summarize 1) findings on the relation of neurobiology to clinical AD; 2) neurobiologic pathways linking risk factors to clinical AD; 3) non-cognitive AD phenotypes including motor function and decision making; 4) the development of a novel drug discovery platform. CONCLUSION: Complexity at multiple levels needs to be understood and overcome to develop effective treatments and preventions for cognitive decline and AD dementia.

Financial and Health Literacy Predict Incident Alzheimer's Disease Dementia and Pathology. - Yu, Lei; Wilson, Robert S; Schneider, Julie A; Bennett, David A; Boyle, Patricia A (J Alzheimers Dis, 2017)
BACKGROUND: Domain specific literacy is a multidimensional construct that requires multiple resources including cognitive and non-cognitive factors. OBJECTIVE: We test the hypothesis that domain specific literacy is associated with Alzheimer's disease (AD) dementia and AD pathology after controlling for cognition. METHODS: Participants were community-based older persons who completed a baseline literacy assessment, underwent annual clinical evaluations for up to 8 years, and agreed to organ donation after death. Financial and health literacy was measured using 32 questions and cognition was measured using 19 tests. Annual diagnosis of AD dementia followed standard criteria. AD pathology was examined postmortem by quantifying plaques and tangles. Cox models examined the association of literacy with incident AD dementia. Performance of model prediction for incident AD dementia was assessed using indices for integrated discrimination improvement and continuous net reclassification improvement. Linear regression models examined the independent association of literacy with AD pathology in autopsied participants. RESULTS: All 805 participants were free of dementia at baseline and 102 (12.7%) developed AD dementia during the follow-up. Lower literacy was associated with higher risk for incident AD dementia (p < 0.001), and the association persisted after controlling for cognition (hazard ratio = 1.50, p = 0.004). The model including the literacy measure had better predictive performance than the one with demographics and cognition only. Lower literacy also was associated with higher burden of AD pathology after controlling for cognition (β= 0.07, p = 0.035). CONCLUSION: Literacy predicts incident AD dementia and AD pathology in community-dwelling older persons, and the association is independent of traditional measures of cognition.

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

National Institute on Aging-Alzheimer's Association guidelines for the neuropathologic assessment of Alzheimer's disease. - Hyman, Bradley T; Phelps, Creighton H; Beach, Thomas G; Bigio, Eileen H; Cairns, Nigel J; Carrillo, Maria C; Dickson, Dennis W; Duyckaerts, Charles; Frosch, Matthew P; Masliah, Eliezer; Mirra, Suzanne S; Nelson, Peter T; et al. (Alzheimers Dement, 2012)
A consensus panel from the United States and Europe was convened recently to update and revise the 1997 consensus guidelines for the neuropathologic evaluation of Alzheimer's disease (AD) and other diseases of brain that are common in the elderly. The new guidelines recognize the pre-clinical stage of AD, enhance the assessment of AD to include amyloid accumulation as well as neurofibrillary change and neuritic plaques, establish protocols for the neuropathologic assessment of Lewy body disease, vascular brain injury, hippocampal sclerosis, and TDP-43 inclusions, and recommend standard approaches for the workup of cases and their clinico-pathologic correlation.
Keywords: Alzheimer Disease; Brain; Consensus Development Conferences, NIH as Topic; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States